Rehabilitation Stroke Arduino System Therapy Glove - Safwan, Mohammad (Journal of Computing Technologies and Creative Content, 2019)
Nowadays, stroke has become one of the leading causes of adult incapacity and stroke is also the top ten causes for hospitalization in Malaysia. Nevertheless, stroke is a disease with a huge concern of sickness in the patients. Arduino Therapy Glove is a device that is used by the patient so it can serve as an assistant device and provide feedback while performing stroke rehabilitation therapy both at home and hospital. Arduino UNO, Arduino Nano, two Bluetooth, and three types of sensors will be used in this project. The main function of the sensor unit is to provide the main unit with information from all sensors that has been connected to the Arduino microcontroller board. The three sensors that connected directly to the Arduino, which are an accelerometer, force sensitive resistor, and flex. Accelerometer function is to measure the perimeter related to force generated from arm movement. Next, the flex sensor will provide the device with the information needed regarding the angle value between lower and upper arm. After that, force sensitive resistor is suitable to detect the muscle force due to muscle flexion and an extension activity.